The efficacy of brief strategic therapy in treating obsessive-compulsive disorder: a case series: Brief strategic therapy and OCD - Proietti, Luca; Aguglia, Andrea; Amerio, Andrea; Costanza, Alessandra; Fesce, Fabio; Magnani, Luca; Serafini, Gianluca; Amore, Mario (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: International guidelines indicate pharmacological therapy and cognitive-behavioral therapy (CBT) as gold standard treatments for obsessive-compulsive disorder (OCD). However, up to 40% patients do not fully respond to CBT, thus manifesting persistent symptomatology. Empirical research reported brief strategic therapy (BST) as a potential treatment for OCD. The aim of the present study is to evaluate the efficacy of BST in treating OCD and to identify the clinical characteristics associated to response. Methods: BST protocol was administered to patients with OCD. During a 24-weeks observational phase, the following scales have been administered at the baseline and every 4 weeks: Yale Brown Obsessive-Compulsive scale (Y-BOCS), Clinical Global Impression, Global Assessment of Functioning, Quality of Life Index, Medical Outcomes Study Short Form 12-item, Clinical Outcomes in Routine Evaluation-Outcome Measure, Generalized Anxiety Disorder Scale, Patient Health Questionnaire - 9 and Somatic Symptom Scale-8. Results: eight patients completed the treatment and a subgroup of five patients obtained clinical remission, defined as Y-BOCS total score < 25. The repeated measures ANOVA performed showed a significant decreased of the Y-BOCS total scores (p<.001). Comparisons between the two subgroups (remitters vs. non-remitters) highlighted some potential baseline characteristics associated with remission: i.e., higher mean level of anxiety, quality of life, physical health, and lower mean level of somatic symptoms and lower prevalence of personality disorders comorbidity. Conclusions: BST could be a useful therapeutic strategy in treating OCD patients. Further studies with larger samples and with long-term follow-up are needed to assess the post-treatment maintenance of clinical effects.